Coping in Nordic Peripheries - on the Spatial Production of Societies - Jørgen Ole Bærenholdt (European Regional Science Association (ERSA), 2003)
In many traditional approaches the notion of “society” has been taken for given as a territorial container of modern society per se, and regional development was only a question of how to organise and distribute within societies. However, increasingly globalisation, flows and networks across borders have been seen as the new dominant forces of the 21st century, and traditional approaches to regional development are seen as trapped in territorial understandings. The paper seeks to develop a third position that highlights the constitutive forces of spatial practices to the development of modernity in Nordic peripheries. Hence, the spatial practices inherent in coping strategies, regional policies, planning and other aspects of regional development are interpreted not as effects or consequences of social orders, but as producers of social orders. Specific focus is given to the constitutive role of the territorial orders of municipalities and the protestant church in the formation of, often surprising, modern orders in Nordic peripheries in the 20th century. The paper draws on and develops empirical and theoretical insights from the UNESCO MOST Circumpolar Coping Processes Project (co-ordinated by the author, see www.unesco.org/most/p91.htm and www.uit.no/MostCCPP).
Keywords: 330